Human resource management and performance at the Indian Railways. Issue 1 (12th February 2018) - Pereira, Vijay Edward; Fontinha, Rita; Budhwar, Pawan; Arora, Bimal
Abstract : Purpose: High-performance work practices (HPWPs) have been well documented within private organisations in developed country economies. Such practices, however, remain under-investigated in the public sector and in emerging economies. The purpose of this paper is to work towards filling this void, by empirically evaluating HPWP within an Indian public sector undertaking (PSU), also the world's largest commercial public sector employer: the Indian Railways (IR). Design/methodology/approach: The authors investigate whether the practices implemented in this organisation are consistent with the idea of HPWPs, and analyse how they are influenced by different stakeholders and ultimately associated with different indicators of organisational performance. The authors focused on six railway zones and interviewed a total of 62 HR practitioners. Findings: The results show that most practices implemented are aligned with the idea of HPWPs, despite the existence of context-specific unique practices. Furthermore, the authors identify the influence of multiple stakeholders in decision making concerning different practices. The authors additionally found that the measurement of performance goes beyond financial indicators and several context-specific non-financial indicators are identified and their social importance is reiterated. Originality/value: Theoretically, this paper utilises and contributes to the resource-based view of firms by identifying a distinctive bundle of competencies in human resources through HPWS in the IR.